EXPRESSIVE SERVICE OF REPETITIONS USED IN THE WORKS OF SH. SEITOV (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The article discusses the role of repetition in the work of Sh.Seitov and his linguo-poetic analysis. Types of repetition are studied by examples.